Blood pressure changes in haemodialysis: the nigerian experience (1998)
The blood pressure changes in haemodialysis were assessed during 59 sessions in 21 patients. Blood pressure was measured with I he corresponding pulse before and subsequently hourly during dialysis, and the patients weights were measured before and after dialysis. The mean systolic blood pressure before dialysis was 170,22 + 29.64mmHg. This showed a statistically sig nificant decrease at l hour. being 167^31.79mmHg (P < 0.002 at 2 hours, being 164.83 + 40.26mmHgwith (P < 0.001). at 3 hours, being 166.84+ 36.94mm Hg (P< 0.001) intradialysis, and immediately after 4 hours of dialysis 166.28 ±35.70mmHg t P < 001). The mean diastolic blood pressure before dialysis of 109.90 + 20.SOmmHg also showed a significant decrease at 1 hour 106.07 + 22.84mmHg (P< 001) 2 hours 105.98+ 22.10mmHg (P < 0.001) and 3 hours intradialysis 107.81 + 25.39mmHg (P< 0.001). These findings suggest that blood pressure changes in haemodialysis are affected by drop in weight that invariably occurs in haemodialysis due to the accompanying process of ultrafiltration